Searching for Neutrinoless Double-Beta Decay of 130Te with CUORE - D. R. Artusa; F. T. Avignone; O. Azzolini; M. Balata; T. I. Banks; G. Bari; J. Beeman; F. Bellini; A. Bersani; M. Biassoni; C. Brofferio; C. Bucci; et al. (Advances in High Energy Physics)
Neutrinoless double-beta (0νββ) decay is a hypothesized lepton-number-violating process that offers the only known means of asserting the possible Majorana nature of neutrino mass. The Cryogenic Underground Observatory for Rare Events (CUORE) is an upcoming experiment designed to search for 0νββ decay of 130Te using an array of 988 TeO2 crystal bolometers operated at 10 mK. The detector will contain 206 kg of 130Te and have an average energy resolution of 5 keV; the projected 0νββ decay half-life sensitivity after five years of livetime is 1.6 × 1026 y at 1σ (9.5 × 1025 y at the 90% confidence level), which corresponds to an upper limit on the effective Majorana mass in the range 40–100 meV (50–130 meV). In this paper, we review the experimental techniques used in CUORE as well as its current status and anticipated physics reach.